Indonesia Pengaruh Profitabilitas, Leverage, Likuiditas, Good Corporate Governance pada Kebijakan Dividen Perusahaan Pertambangan Tahun 2021-2023: Pengaruh Profitabilitas, Leverage, Likuiditas, Good Corporate Governance Pada Kebijakan DividennPerusahaan Pertambangan Tahun 2021-2023 - -, Pujiyanti; Wijayanti, Anita; Rachmawati Dewi, Riana (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2025)
The purpose of this study is to test and analyze the effect of profitability, leverage, likuidity, and good corporate governance. This study is a quantitative study.  The date obtained from the financial statements of mining companies listed on the Indonesia Stock Exchange (IDX) in the period 2021-2023. The population of study is mining companies listed on the Indonesia Stock Exchange (IDX) in period 2021-2023. Sampling usingt the purposive sampling method and the sampling used ini this study was 21 companies. The technical data analysis used multiple linear regression analysis obtained with SPSS version 21. The results, leverage of this study indicate on dividend policy. While likuidty, good corporate governance do not effect dividend policy.